KEPUTUSAN KONSUMEN DALAM PEMILIHAN PAKET UMRAH DI PT. SMEVASINDO HOLIDAY PEKANBARU - Shara Novia Annas; Andri Sulistyani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
PT. Smevasindo Holiday Pekanbaru is one of the many travel agency companies that are engaged in organizing pilgrimage and umrah trips in the city of Pekanbaru. Many factors are taken into consideration by consumers in choosing an Umrah travel agency that is in accordance with their wishes. These factors consist of internal and external factors. Internal factors, namely culture, social, personality, psychological and external factors, namely products, prices, promotions, places. This study aims to identify what factors influence consumer decisions in the selection of umrah packages at PT. Smevasindo Holiday Pekanbaru. This research uses quantitative methods. The sampling method used in this study was purposive sampling, with the number of samples or respondents as many as 100 people obtained by using Slovin's adequacy formula. Data collection techniques in this study used questionnaires, observation, and documentation. This study uses a measurement technique with a Likert scale to measure attitudes, opinions, and perceptions of a person or group of people about social phenomena. The results of the study show that the price factor greatly influences consumer decisions in the selection of umrah packages at PT. Smevasindo Holiday based on consumer responses to price factors with a total score of 889 in the range of scores of 840 - 1,000 with the category strongly agree. Keywords: Consumer Decisions, Travel Bureau, Umrah Package